216k views
3 votes
What equation makes this true -3(x-4)+x =2x-12

1 Answer

5 votes

Answer:


x = 6

Explanation:

Step 1: Distribute


-3(x - 4) + x = 2x - 12


(-3 * x) + (-3 * -4) + x = 2x - 12


(-3x) + (12) + x = 2x - 12

Step 2: Combine like terms


(-3x) + (12) + x = 2x - 12


(-3x + x) + 12 = 2x - 12


(-2x) + 12 = 2x - 12

Step 3: Add 12 to both sides


(-2x) + 12 + 12 = 2x - 12 + 12


(-2x) + 24 = 2x

Step 4: Add 2x to both sides


(-2x + 2x) + 24 = 2x + 2x


24 = 4x

Step 5: Divide both sides by 4


(24 / 4) = (4x / 4)


(6) = x

Answer:
x = 6

User Gowtham Sooryaraj
by
5.1k points